Is Rifampin Use Associated With Better Outcome in Staphylococcal Prosthetic Valve Endocarditis? A Multicenter Retrospective Study. (24th July 2020) - Le Bot, Audrey; Lecomte, Raphaël; Gazeau, Pierre; Benezit, François; Arvieux, Cédric; Ansart, Séverine; Boutoille, David; Le Berre, Rozenn; Chabanne, Céline; Lesouhaitier, Matthieu; Dejoies, Loren; Flecher, Erwan; et al.
Abstract: Background: International guidelines recommend rifampin-based combinations for staphylococcal prosthetic valve endocarditis (PVE). However, no robust clinical data support this recommendation, and rifampin tolerability is an issue. We aimed to evaluate the impact of rifampin for the treatment of staphylococcal PVE. Methods: An observational retrospective cohort study of all adults with staphylococcal PVE (modified Duke criteria) was conducted in 3 referral centers for endocarditis, during years 2000–2018. Primary outcome measurement was 1-year mortality. Results: We enrolled 180 patients with PVE due to Staphylococcus aureus (n = 114, 63.3%), or coagulase-negative staphylococci (n = 66, 36.7%), on bioprosthesis (n = 111, 61.7%), mechanical valve (n = 67, 37.2%), or both (n = 2). There were 132 males (73.3%), and mean age was 70.4 ± 12.4 years. Valvular surgery was performed in 51/180 (28.3%) cases. Despite all isolates were susceptible to rifampin, only 101 (56.1%) were treated with rifampin, for a median duration of 33.0 days, whereas 79 (43.9%) received no rifampin. Baseline characteristics were similar in both groups. One-year mortality was, respectively, 37.6% (38/101), and 31.6% (25/79), in patients treated with, or without, rifampin ( P = .62). Relapse rates were 5.9% (6/101), and 8.9% (7/79), P = .65. Patients treated with rifampin had longer hospital length-of-stay: 42.3 ± 18.6 vs 31.3 ± 14.0 days ( P < .0001). On multivariate analysis, only cerebral emboli (odds ratio [OR] 2.95, 95% confidence interval [CI], 1.30–6.70, P = .009), definite endocarditis (OR 7.15, 95% CI, 1.47–34.77, P = .018), and methicillin-resistant S. aureus (OR 6.04, 95% CI, 1.34–27.26, P = .019), were associated with 1-year mortality. Conclusions: A large proportion (43.9%) of staphylococcal PVE received no rifampin. One-year survival and relapse rates were similar in patients treated with or without rifampin. Abstract : In this cohort study of 180 patients with staphylococcal prosthetic valve endocarditis, rifampin use was associated neither with better survival nor with lower risk of relapse. Cerebral emboli, definite endocarditis, and methicillin-resistant S. aureus were independently associated with 1-year mortality.